Polishing the Therapy of Onychomycosis Induced by Candida spp.: Amphotericin B-Loaded Nail Lacquer - Aleph M. S. Souza; Renato C. A. Ribeiro; Gleyse K. L. O. Pinheiro; Francisco I. Pinheiro; Wógenes N. Oliveira; Luanda B. F. C. Souza; André L. Silva; Lucas Amaral-Machado; Éverton N. Alencar; Guilherme M. Chaves; Eryvaldo S. T. Egito (MDPI AG, 2021)
Onychomycosis induced by Candida spp. has several limitations regarding its treatment. Nail lacquers display the potential to overcome these drawbacks by providing therapeutic compliance and increasing local drug bioavailability. Thus, this work aimed to produce a nail lacquer loaded with Amphotericin B (AmB) and evaluate its performance. The AmB-loaded nail lacquer was produced and preliminarily characterized. An AmB quantification method was developed. Stability, drug release, permeability and anti-Candida activity assays were conducted. The analytical method validation met the acceptance criteria. The drug loading efficiency was 100% (0.02 mg/g of total product), whereas the AmB stability was limited to ≅7 days (≅90% remaining). The nail lacquer displayed a drying time of 187 s, non-volatile content of around 20%w/w, water-resistance of approximately 2%w/w of weight loss and satisfactory in vitro adhesion. Moreover, the in vitro antifungal activity against different Candida spp. strains was confirmed. The AmB release and the ex vivo permeability studies revealed that AmB leaves the lacquer and permeates the nail matrix in 47.76 ± 0.07% over 24 h. In conclusion, AmB-loaded nail lacquer shows itself as a promising extemporaneous dosage form with remarkable anti-Candida activity related to onychomycosis.